The ecological role of small rainfall events in a desert grassland. Issue 8 (25th February 2015) - Petrie, M. D.; Collins, S. L.; Litvak, M. E.
Abstract: The frequency, magnitude and intensity of precipitation events are known to influence dryland ecosystems; yet, the majority of these rain events are small (<5 mm), and their role in driving biotic and abiotic processes remains unclear. To explore the effects of small rain events that occur between larger events on ecosystem processes, we experimentally manipulated small rainfall events in a mixed Bouteloua eriopoda and Bouteloua gracilis desert grassland. We experimentally removed all events <3.8 mm from treatment plots during a dry monsoon (2012), and to assess potential legacy effects, we added a similar magnitude of small rainfall events in 3.8‐mm increments to the same treatment plots during a subsequent wet monsoon (2013). No difference in aboveground productivity occurred between ambient and treatment plots when small events were eliminated in 2012. However, soil moisture, soil organic carbon, available nitrogen and extracellular enzyme activity for phosphate mobilization were all lower in treatment relative to ambient plots. In 2013, treatment plots that received supplemental small events had lower aboveground productivity, soil moisture and soil N availability than ambient plots. We hypothesize that legacy effects from the removal of small events in 2012 limited the ability of these plots to respond to higher, supplemented rainfall in 2013. Therefore, a reduction in small precipitation events – which may be caused by changing rainfall properties or increasing rates of evaporation in a warming climate – may intensify some deleterious effects of dry monsoons, and inhibit grassland recovery in subsequent years with higher rainfall. Copyright © 2015 John Wiley & Sons, Ltd.